Gangguan Skizofrenia Paranoid - Nisfal Putri Amalia; Juniarti Juniarti (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Schizophrenia is a complex psychiatric disorder that disrupts cognition, emotion, perception, and behavior, significantly affecting daily functioning and social interaction. Paranoid schizophrenia, a well-recognized subtype, is characterized by persistent paranoid delusions, frequently accompanied by hallucinations—most commonly auditory—and other perceptual disturbances, often leading to unpredictable or aggressive behaviors. A 34-year-old male patient, Mr. A, was brought to Cut Meutia General Hospital on February 9, 2024, by his father and the village chief due to episodes of aggression. The patient reported that his behavior occurred because a creature was controlling his body and disturbing him. His family indicated that he had experienced similar episodes in the past and had previously been hospitalized for the same condition. Based on established clinical guidelines, he was diagnosed with paranoid schizophrenia. Pharmacological management was initiated, including risperidone, clozapine, lodemer injection, diazepam injection, divalproex, and trihexyphenidyl, targeting psychotic symptoms, agitation, and behavioral disturbances, with the aim of stabilizing his mental state, preventing further aggressive episodes, and supporting overall functional recovery.